Applications of high-frequency resolution, wide-field VLBI: observations of nearby star-forming galaxies & habitable exoplanetary candidates - Rampadarath, Hayden (Curtin University, 2014)
In this thesis, I investigate the radio source populations and properties of two nearby star-forming galaxies. In addition, I present an independent method to estimate the supernova and massive star-formation rates of star-forming galaxies. This study makes use of a new technique that allows multiple astronomical objects to be simultaneously observed via very high resolution radio interferometry. Furthermore, using this technique I develop a new method to search for evidence of extraterrestrial intelligence from habitable planetary candidates.